Photovoltaic fed multilevel inverter using reverse voltage topology for standalone systems - M. Arun Noyal Doss; K Mohanraj; Sayantan Bhattacharjee; Maulik Tiwari; Devashish Vashishtha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Multilevel Inverters are generally utilized for medium voltage and high power applications. Invented in 1975, MLIs have brought huge change in the field of Electrical and Electronics. It contains distinctive topologies. This paper proposes a photovoltaic aided multilevel inverter with Reverse Voltage topology with diminished number of switches. In comparison to other existing topologies this topology utilizes minimum number of switches and less number of carrier signals which in turns diminishes the complexity of the system as well as cost. The proposed framework contains five MOSFETs, five diodes to create eleven levels. In this topology the SPWM strategy has been utilized. This topology utilizes one sine wave and five triangular waves, which is half in comparison to the existing topologies. As sustainable power sources can be utilized for multilevel inverter, photovoltaic cell has been utilized. The MATLAB recreation for both solar powered module and Multilevel inverter has been appeared alongside the equipment approach.